Arbitrary Lagrangian - Eulerian formulation of the equations system which modeling the interaction of airflow with the pulmonary alveolus - Vallejos, Raúl E. Reupo (2017)
In this article, we formulate a physiological process through a two-dimensional fluid-structure interaction problem between the airflow and the pulmonary alveolus in the Eulerian-Lagrangian Arbitrary (ALE) frame.This problem arises by coupling the equations of the fluid and the structure, described by the Navier-Stokes equations of evolution for incompressible flows, and an equilibrium equation, respectively.